(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
The laminar fluid flow and convective heat transfer are numerically investigated for single phase flow in corrugated duct. The governing equations of fluid flow are discretized using finite volume method based on SIMPLE algorithm and solved using CFD code. Also, the considered computational domain is two dimensional channel which corrugated angles, heat transfer and Reynolds numbers are used as design variables. The obtained results show that the Nusselt number increase with an increase in the Reynolds numbers, angles of corrugation and heat flux. However, the friction factor decreases versus the Reynolds numbers. Numerical results are compared with those of straight channel and there is a good agreement.